Ethical AI Implementation in Educational Settings: Balancing Innovation with Academic Integrity and Student Privacy - Henny Uswatun Hasanah; Ahmad Munir; Ali Mustofa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The rapid integration of artificial intelligence (AI) into education necessitates urgent ethical implementation frameworks, especially in vocational systems of developing countries like Indonesia, where workforce readiness meets digital transformation. The purpose of this study is to address gaps in ethical AI governance within Indonesian vocational schools (SMK). A sequential explanatory mixed-methods design was employed, involving 847 stakeholders from 34 provinces and eight in-depth SMK case studies. Findings reveal moderate national AI ethics awareness (M=2.83), with significant regional gapsâ€”from Java (3.01) to Papua (2.34)â€”and a critical privacy paradox: high concern (M=3.67) coexists with low legal literacy (28.9%). Students actively use AI for academic support (64.3%) but lack institutional guidance, while teachers face identity crises requiring deeper pedagogical reform beyond technical training. The proposed ETIKA-SMK framework, co-developed with experts, received strong validation (relevance 4.3/5.0; innovation 4.4/5.0) and showed improvements in ethical policy compliance (67.8%) and cybersecurity practices (58.7%) at pilot schools. The study highlights the need for differentiated implementation strategies, as 50% of SMKs fall into â€œTraditionalâ€ or â€œStrugglingâ€ categories requiring foundational capacity-building. It concludes that ethical AI integration must be grounded in local contexts, institutional capacities, and cultural values, rather than adopting standardized global models unsuitable for low-resource educational environments.